Breath Counting Method using Object Detection Algorithm - Imaizumi, Nanami; Ohyama, Futoshi; Matsumoto, Hiroki (International Symposium on Communications and Information Technologies (Online), 2024)
In the medical field, the "respiratory rate" of hospitalized patients is measured as one of the vital signs. Respiratory rate is one of the most important items. However, measurement respiratory rate is many burdens of medical personnel because it is done visually. We investigate a method to automatically measure respiratory rate to reduce the burden of medical personnel. An object detection algorithm is applied to the images obtained from the video camera. It is found that it is possible to measure respiratory rate by detecting the width of the subjects bounding box obtained by this method. We propose a method for measuring respiratory rate using this method.